Passions, Sympathy and Print Culture Public Opinion and Emotional Authenticity in Eighteenth-Century Britain - Kerr, Heather; Lemmings, David; Phiddian, Robert; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
.
Keywords: Great Britain-History.; Psychology -- History; Emotions; British literature; History, Modern; Journalism; Emotion